Academic Senate Minutes 2004-04-22 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 3/4/04 and 3/18/04 approved. From S&F: Staggered Membership proposal for APC and EPC approved. Chair's Report. Lobbying and Use of Appropriated Federal Funds policy approved. Policy on Copyright Ownership approved. Provost report. Vice President for Administration and Finance report. President's Report. An Assembly Budget Hearing report. 40th anniversary of the Senate noted. Winner of Excellence in Teaching Award announced.